Clinical Case and Literature Review of a Potentially Life-Threatening Complication Derived from Mouth Floor Hematoma after Implant Surgery - Carreira-Nestares, Beatriz; Urquiza-Fornovi, Irene; Carreira-Delgado, Manuel Carlos; Gutierrez-Díaz, Ramón; Sánchez-Aniceto, Gregorio (European Dental Research and Biomaterials Journal, 2023)
The placement of dental implants is a safe and predictable procedure when performed by qualified staff. The incidence of complications derived from this type of surgery has increased due to the greater number of patients undergoing dental rehabilitation treatments in recent years. Floor of the mouth hematoma is a rare, but potentially fatal, complication that every oral surgeon should recognize for early diagnosis. As part of the clinical case presented here, two implants were removed and a hemorrhage in the floor of the mouth was found, which required an urgent intervention to control the bleeding. Two independent researchers conducted an electronic search of the available scientific evidence in relation to bleeding of the floor of the mouth in dental implant surgery. The research included references, which were written in English or Spanish, and published up to December 2022. Case reports, case series, systematic reviews, and meta-analysis were part of the inclusion criteria. Sixty-four bibliographic references were identified, and 39 full-text articles were selected. There were 30 cases of floor of the mouth hematoma in relation to implant surgery. In 13 patients the main location was interforaminal, in 5 in the canine area, in 6 in the incisor area, and in 6 in the molar premolar region. All cases were caused by perforation of the cortical bone or surgical manipulation (disruption of the periosteum, perforation of the sublingual mucosa by the stiff suture). The sublingual artery was most frequently involved. The clinical sign observed in all cases was elevation of the floor of the mouth. In 21 of the cases there was airway involvement, so the main treatment was intubation or tracheostomy. Floor of the mouth hematoma may be one complication associated with implant surgery. Given the seriousness of this clinical picture, early detection by the dentist and hospital referral are essential. Warning signs are sudden swelling of the floor of the mouth or submandibular area, accompanied by dysphagia and dyspnea.
Keywords: dental implant; hematoma; hemorrhage; floor of mouth